Famous fiction for you : Book 2 - Scott, Rosemary; Delioğlu, Mustafa (Istanbul : Orient Press, 1997)
Different fiction.
Amanda and the wounded birds -- sweet caroline -- the old flame -- angela-an inverted love story -- storm warning -- eveline -- the fury.